2019
DOI: 10.1002/ecy.2571
|View full text |Cite
|
Sign up to set email alerts
|

Post‐fire forest regeneration shows limited climate tracking and potential for drought‐induced type conversion

Abstract: Disturbance such as wildfire may create opportunities for plant communities to reorganize in response to climate change. The interaction between climate change and disturbance may be particularly important in forests, where many of the foundational plant species (trees) are long‐lived and where poor initial tree establishment can result in conversion to shrub‐ or graminoid‐dominated systems. The response of post‐disturbance vegetation establishment to post‐disturbance weather conditions, particularly to extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 63 publications
2
48
0
Order By: Relevance
“…Using physiologically based simulations in the northeastern United States, Liang et al () reported that disturbances may expedite species' recruitment into new sites, but they had little effect on the velocity of simulated range boundary shifts. Following fires in California that occurred since 2004, Young et al () found little evidence of disturbance‐mediated vegetation community reorganization on range shifts, from either low sensitivity of species to post‐disturbance weather or widespread recruitment declines precipitated by unusually dry conditions. Interactions between climate change and disturbances warrant further investigation as management practices will need to be adapted to a changing climate, particularly to facilitate migration.…”
Section: Discussionmentioning
confidence: 99%
“…Using physiologically based simulations in the northeastern United States, Liang et al () reported that disturbances may expedite species' recruitment into new sites, but they had little effect on the velocity of simulated range boundary shifts. Following fires in California that occurred since 2004, Young et al () found little evidence of disturbance‐mediated vegetation community reorganization on range shifts, from either low sensitivity of species to post‐disturbance weather or widespread recruitment declines precipitated by unusually dry conditions. Interactions between climate change and disturbances warrant further investigation as management practices will need to be adapted to a changing climate, particularly to facilitate migration.…”
Section: Discussionmentioning
confidence: 99%
“…Drought-induced canopy mortality is well-established (Allen et al, 2015;Anderegg et al, 2013), and recent studies have quantified the impacts of prolonged drought (Redmond, Weisberg, Cobb, & Clifford, 2018) and postfire drought conditions (Stevens-Rumann et al, 2017;Young et al, 2019) on regeneration. However, relatively little is known about the consequences of reduced snowpack and early season frost damage on canopy mortality and regeneration response, although these phenomena may become more common as the climate warms (Woldendorp, Hill, Doran, & Ball, 2008)-leading to root mortality and nutrient loss (Decker, Wang, Waite, & Scherbatskoy, 2003), needle and bud injury (Man, Kayahara, Dang, & Rice, 2009), canopy mortality (Buma, 2018), and seedling mortality (Camarero & Gutiérrez, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…, Young et al. ). Therefore, it is likely that regional shrub influences not only are stronger than measured in this study, but also may become increasingly important under future climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Because shrub‐free areas are rare in stand‐replacing fire patches of the Sierra Nevada (Young et al. ), we quantified juvenile conifer growth across a gradient of shrub competition rather than comparing high‐shrub areas to shrub‐free areas. To ensure that environmental conditions were similar across sites, we limited sites to fire footprints that met the following requirements: between the North and South forks of the American River; >400 ha in size; 5–50 yr old; within the Tahoe or Eldorado National Forests; not planted or herbicided following fire; and containing identifiable shrub fields surrounded by mixed‐conifer forest according to satellite imagery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation